(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The word hacker generally characterize the practice or performance of investigating & carry out trial with computer networks as computer communications grew more ubiquitous with the emergence of the Internet. However, when devices with tools and connected network became more commercialized, the system also became assets with ostensible limitations, & violating such borders became illegal. The number of programs teaching ethical hacking is rapidly increasing. The requirement for a comprehensive understanding of tactics and assailants is at the heart of the case for training in ethical hacking field. Many peoples argue, however, that getting training in offensive hacking skills advances communal menace by promising followers to take part in illegitimate behaviour. Ethics instruction pervades associated curricula, according to proponents of teaching ethical hacking, giving students enough preparation to recognize the hazards and adopt healthy actions. This article looks at ways to reduce the danger of students using abilities learned in an ethical hacking course to perform illegal activities outside of the classroom.